Thermoelectric properties of silicon and recycled silicon sawing waste - He, Ran; Heyn, Wieland; Thiel, Felix; Perez, Nicolas; Damm, Christine; Pohl, Darius; Rellinghaus, Bernd; Reimann, Christian; Beier, Maximilian; Friedrich, Jochen; Zhu, Hangtian; Ren, Zhifeng; et al. (Journal of Materiomics, 2019)
Large-scale-applicable thermoelectric materials should be both self-sustaining, in order to survive long-term duty cycles, and nonpolluting. Among all classes of known thermoelectric materials, these criteria reduce the available candidate pool, leaving silicon as one of the remaining options. Here we first review the thermoelectric properties of various silicon-related materials with respect to their morphologies and microstructures. We then report the thermoelectric properties of silicon sawing wastes recycled from silicon wafer manufacturing. We obtain a high power factor of ∼32 μW cm−1 K−2 at 1273 K with 6% phosphorus substitution in the Si crystal, a value comparable to that of phosphorus-doped silicon-germanium alloys. Our work suggests the large-scale thermoelectric applicability of recycled silicon that would otherwise contribute to the millions of tons of industrial waste produced by the semiconductor industry.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Nanostructure; Power factor; Sawing waste; Silicon; Thermoelectric